An Atypical Presentation of Sporadic Jejunal Burkitt’s Lymphoma - Pratik Naik; James Wang; Michael J. Brazeau; Domingo Rosario (Case Reports in Gastrointestinal Medicine)
Burkitt’s lymphoma is a very aggressive type of B-cell NHL with replication approaching 100%. Primary gastrointestinal lymphoma is rare. In our case, a 24-year-old male initially presented with symptomatic anemia. He was initially evaluated with colonoscopy and EGD, both of which were unremarkable. A capsule endoscopy was then performed to further evaluate his significant anemia which revealed friable inflamed ulcerated mass in the jejunum. A push enteroscopy was then performed to obtain tissue from the jejunal mass. Biopsy results and immunohistochemical stains were consistent with Burkitt’s lymphoma. PET/CT scan revealed only jejunal involvement. Treatment consisted of bowel resection prior to chemotherapy due to concern for perforation with chemotherapy. Patient achieved complete remission after the treatment.